Connected macroalgal‐sediment systems: blue carbon and food webs in the deep coastal ocean. Issue 3 (23rd May 2019) - Queirós, Ana Moura; Stephens, Nicholas; Widdicombe, Stephen; Tait, Karen; McCoy, Sophie J.; Ingels, Jeroen; Rühl, Saskia; Airs, Ruth; Beesley, Amanda; Carnovale, Giorgia; Cazenave, Pierre; Dashfield, Sarah; et al.
Abstract: Macroalgae drive the largest CO2 flux fixed globally by marine macrophytes. Most of the resulting biomass is exported through the coastal ocean as detritus and yet almost no field measurements have verified its potential net sequestration in marine sediments. This gap limits the scope for the inclusion of macroalgae within blue carbon schemes that support ocean carbon sequestration globally, and the understanding of the role their carbon plays within distal food webs. Here, we pursued three lines of evidence (eDNA sequencing, Bayesian Stable Isotope Mixing Modeling, and benthic‐pelagic process measurements) to generate needed, novel data addressing this gap. To this end, a 13‐month study was undertaken at a deep coastal sedimentary site in the English Channel, and the surrounding shoreline of Plymouth, UK. The eDNA sequencing indicated that detritus from most macroalgae in surrounding shores occurs within deep, coastal sediments, with detritus supply reflecting the seasonal ecology of individual species. Bayesian stable isotope mixing modeling [C and N] highlighted its vital role in supporting the deep coastal benthic food web (22–36% of diets), especially when other resources are seasonally low. The magnitude of detritus uptake within the food web and sediments varies seasonally, with an average net sedimentary organic macroalgal carbon sequestration of 8.75 g C·m −2 ·yr −1 . The average net sequestration of particulate organic carbon in sediments is 58.74 g C·m −2 ·yr −1, the two rates corresponding to 4–5% and 26–37% of those associated with mangroves, salt marshes, and seagrass beds, systems more readily identified as blue carbon habitats. These novel data provide important first estimates that help to contextualize the importance of macroalgal‐sedimentary connectivity for deep coastal food webs, and measured fluxes help constrain its role within global blue carbon that can support policy development. At a time when climate change mitigation is at the foreground of environmental policy development, embracing the full potential of the ocean in supporting climate regulation via CO2 sequestration is a necessity.